Meningkatkan Kepatuhan Wajib Pajak UMKM Pada Era New Normal Melalui Pemberian Insentif Pajak, Peningkatan Kondisi Keuangan Dan Kesadaran Pajak - Budi Riyanti; Erna Sudarmawanti (Politeknik Ganesha Medan, 2022)
The Covid-19 pandemic has put tremendous pressure on people, resulting in a decrease in people's purchasing power and a decrease in their ability to fulfill their tax obligations, including the MSME sector. In the context of PEN, the government provides various policies for MSMEs, namely by providing DTP tax incentives, it is hoped that by providing tax incentives, MSMEs can still survive during the pandemic so that in the new normal era, MSME financial conditions will become more stable and can fulfill their tax obligations. However, without being based on high tax awareness, even though financial conditions are stable, MSME taxpayer compliance will be difficult to realize. The purpose of this study is to examine how the effect of providing tax incentives, financial conditions and tax awareness on MSME taxpayer compliance in the new normal era. This study uses a population of MSMEs in Salatiga City with a sample of 100 MSMEs that have taken advantage of tax incentives. Purposive sampling method was used to determine respondents. The data used is primary data with quantitative analysis techniques. Hypothesis testing using multiple regression analysis. The data is processed with the help of the statistical package for social science (SPSS) for windows. The results of the study show that tax incentives and tax awareness have a positive effect on MSME taxpayer compliance, while financial conditions have no effect on MSME taxpayer compliance in the new normal era. Although tax incentives have not been able to improve the financial condition of MSMEs in the new normal era, but tax incentives are considered quite effective in supporting the PEN program launched by the government of their tax obligation.